Regulation of prohepcidin processing and activity by the subtilisin-like proprotein convertases Furin, PC5, PACE4 and PC7. Issue 11 (29th July 2008) - Scamuffa, N; Basak, A; Lalou, C; Wargnier, A; Marcinkiewicz, J; Siegfried, G; Chrétien, M; Calvo, F; Seidah, N G; Khatib, A-M
Abstract : Background and aims: Hepcidin is an iron homoeostasis regulator peptide. Loss-of-function mutations cause juvenile haemochromatosis while its over-expression results in anaemia. However, the mechanism and function of preprohepcidin conversion to mature hepcidins (25, 22 and 20 amino acid C-terminal peptides) are not well known. After removal of the signal peptide, the first proteolytic cleavage occurs within the basic motif RRRRR 59 DT, suggesting the involvement of proprotein convertase (PC) family members in this process. Methods and results: Using cell transfection experiments, the processing of preprohepcidin in the human hepatocyte line Huh-7 was found to be inhibited by the Furin inhibitors serpin α1-antitrypsin (α1-PDX) and prosegment preproFurin (ppFurin). Site-directed mutagenesis analysis confirmed the RRRRR 59 DT preprohepcidin cleavage site. In parallel, the lack of preprohepcidin processing found in the PC activity-deficient cell line LoVo was restored by the expression of Furin, paired basic amino acid cleaving enzyme 4 (PACE4), PC5 or PC7. This finding is consistent with the in vitro digestions of a synthetic peptide mimicking the cleavage site of preprohepcidin. In addition, during mouse embryonic development the major expression of hepcidin found in the liver coincided with that of Furin. While hepcidin induces the degradation of the iron transporter ferroportin, its RRRRR 59 to SSSSS 59 mutant is not active. Conclusions: These results demonstrate the key role of the convertases Furin, PACE4, PC5 and/or PC7 in the generation and secretion of active hepcidin and suggest that the control of hepcidin processing as a potential therapeutic/diagnostic strategy in hepcidin-related disorders such as haemochromatosis, inflammatory diseases, anaemia and cancer.